Persepsi Penumpang Angkutan Umum Kota (Pete-Pete) Terhadap Kualitas Pelayanan Trayek Terminal Malengkeri – Cendrawasih - Unhas, Makassar - Venesya Agatha Lembang (Paulus Civil Engineering Journal, 2025)
The proper management of transportation is an important issue that must be considered by the country and service providers. Public transportation that meets the needs of the community. The purpose of this study is to understand passenger characteristics and passengers' perceptions of the quality of public transportation services on the Malengkeri Terminal – Cendrawasih – Unhas Campus route. Data collection was conducted on working days through passenger questionnaire forms. Data analysis was carried out using Microsoft Excel and the Servqual approach (reliability, responsiveness, empathy, tangibles, and assurance). The characteristics of passengers using public transportation (pete-pete) on the Unhas-Cendrawasih-Malengkeri route are dominated by female passengers aged 26-35, working as private employees, and holding a bachelor's degree. Passengers' perception of the quality of public transportation service (pete-pete) on the Malengkeri Terminal – Cendrawasih – Unhas route is highest in the tangibles dimension, with the average highest expectation also in tangibles. The empathy and assurance dimensions of quality, reality/perception, and expectation have good values. The pete-pete transportation always ensures good cleanliness both inside and outside the vehicle, which is rated well. Meanwhile, the drivers always maintain a clean and neat appearance, which passengers also rate well. Assurance in pete-pete transportation, especially in the empathy service dimension, indicates a lack of attention and passenger safety maintenance, which is considered less satisfactory.